Can policy interact with culture? Minimum wage and the quality of labor relations - Philippe Aghion; Yann Algan; Pierre Cahuc (Institute for the Study of Labor (IZA), 2008)
Can public policy interfere with culture, such as beliefs and norms of cooperation? We investigate his question by evaluating the interactions between the State and the Civil Society, focusing on the labor market. International data shows a negative correlation between union density and the quality of labor relations on one hand, and state regulation of the minimum wage on the other hand. To explain this relation, we develop a model of learning of the quality of labor relations. State regulation crowds out the possibility for workers to experiment negotiation and learn about the true cooperative nature of participants in the labor market. This crowding out effect can give rise to multiple equilibria: a good equilibrium characterized by strong beliefs in cooperation, leading to high union density and low state regulation; and a bad equilibrium, characterized by distrustful labor relations, low union density and strong state regulation of the minimum wage. We then use surveys on social attitudes and unionization behavior to document the relation between minimum wage legislation and the beliefs about the scope of cooperation in the labor market.
urn:nbn:de:101:1-2008092948
Keywords: J30; 330; Social capital; quality of labor relations; trade unions; minimum wage; Arbeitsmarktpolitik; Mindestlohn; Arbeitsbeziehungen; Gewerkschaftsbewegung; Kooperation; Soziale Werte; OECD-Staaten